Um olhar interpretativo para as canções de Arthur Bosmans - Ligia Ishitani Silva (2012)
This dissertation presents a study of the vocal music by composer Arthur Bosmans, born in Belgium in 1908. Bosmans was naturalized Brazilian and lived in Belo Horizonte, exercising, especially in this city, an outstanding performance as a conductor, composer and teacher. Despite the recent studies on Arthur Bosmans, there is a lack of a bibliography that specifically discusses his works for singers. Thus, I elaborate a catalog of his songs, available at the end of this dissertation. Among the songs, three were chosen to be analyzed, concerning interpretation. They are Sérénade and Lebens-Leitmotiv (1934-35), and also Meu Nordeste (1979), written in chronologically opposite moments in the composer's life. An analysis of the songs seeking relations between the poem and the music was accomplished. Preceding them, a chapter was devoted to a reflection about interpretation, involving not only its concept, but also the reasons why it differs from one person to another.